2021
DOI: 10.1161/circresaha.120.317046
|View full text |Cite
|
Sign up to set email alerts
|

NAD + Repletion Reverses Heart Failure With Preserved Ejection Fraction

Abstract: Rationale: Heart failure with preserved ejection fraction (HFpEF) is a mortal clinical syndrome without effective therapies. We recently demonstrated in mice that a combination of metabolic and hypertensive stress recapitulates key features of human HFpEF. Objective: Using this novel preclinical HFpEF model, we set out to define and manipulate metabolic dysregulations occurring in HFpEF myocardium. Methods and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 39 publications
10
111
0
Order By: Relevance
“…Another promising NAD + booster candidate is NR. NR fueled the NAD + pool and exerted protective effects in experimental mouse models of HFrEF and HFpEF (Diguet et al, 2018;Tong et al, 2021). NR, whether given in a preventive or in a treatment context, conferred beneficial effects on liver steatosis by upregulating Sirt1 expression and replenishing NAD + concentration (Gariani et al, 2016).…”
Section: Nicotinamide Ribosidementioning
confidence: 99%
“…Another promising NAD + booster candidate is NR. NR fueled the NAD + pool and exerted protective effects in experimental mouse models of HFrEF and HFpEF (Diguet et al, 2018;Tong et al, 2021). NR, whether given in a preventive or in a treatment context, conferred beneficial effects on liver steatosis by upregulating Sirt1 expression and replenishing NAD + concentration (Gariani et al, 2016).…”
Section: Nicotinamide Ribosidementioning
confidence: 99%
“…We found that PDH activity was significantly increased in mitochondria from KO mice on a HFD relative to both WT diet groups ( Figure C ). Elevated PDH enzyme activity is typically associated with decreased inhibitory phosphorylation at Ser-293 [2] , however we detected no difference in PDH phosphorylation between WT and KO mice on either diet ( Figure C ). Instead, we found a significant increase in PDH hyperacetylation in HFD-fed WT mice relative to LFD controls, and a significant decrease in PDH acetylation in both KO diet groups ( Figure C ).…”
Section: Lettermentioning
confidence: 58%
“…Deleterious changes in energy metabolism underpin the development of heart failure with preserved ejection fraction (HFpEF) [1] . Studies on two recently developed murine models of HFpEF have reported altered cardiac fuel substrate utilization, culminating in changes to the relative oxidation rates of fatty acids, ketone bodies, and glucose in failing hearts [2,3] . These two distinct murine HFpEF models are also characterized by increased mitochondrial protein acetylation, a reversible posttranslational modification that is commonly linked to reduced metabolic enzyme activity [2,3] .…”
Section: Lettermentioning
confidence: 99%
See 2 more Smart Citations